Efektivitas penggunaan Lagu Pop Bahasa Inggris Terhadap Kemampuan Menyimak Siswa pada Kelas Tujuh SMP Negeri 38 Palembang - Maya Yuliana; Jaya Nur Iman; Nike Anggraini (Indra institute Research & Publication, 2022)
The objectives of this research were to know (1) whether there was any significant improvement in students’ listening comprehension achievement after being taught by using English pop songs at the seventh grade of SMP Negeri 38 Palembang; (2) whether there was any significant mean difference in students’ listening comprehension achievement between the students who are taught by using English pop songs and those who are not. The research design of this research was a quasi-experimental design. The population of this research was all the seventh-grade students of SMP Negeri 38 Palembang. Sample of this research was class 7.1 as the control group, which consisted of 34 students, and class 7.2 as the experimental group, which consisted of 34 students. Technique of collecting the data used in this research was pre-test and post-test. Then, the data were analyzed by using paired sample t-test and independent sample t-test through SPSS v.25 programs. The result of paired sample t-test in the experimental group showed that t-obtained was 19,380 > t-table (df = 33) at the significance level of 0,05 was 2,034. It means that there was a significant improvement in students' listening comprehension achievement after being taught by using English pop songs. Furthermore, the result of the independent sample t-test showed that t-obtained was 7,858 > t-table (df = 66) at the significance level of 0,05 was 1,996. It means that there was a significant mean difference between the experimental group and the control group. The research findings showed that teaching listening using English pop songs was effective in improving students’ listening comprehension achievement at the seventh grade of SMP Negeri 38 Palembang.